Characteristics of Selected Antioxidative and Bioactive Compounds in Meat and Animal Origin Products - Bartosz Kulczyński; Andrzej Sidor; Anna Gramza-Michałowska (Antioxidants, 2019)
Meat and meat products have a high nutritional value. Besides major components, meat is rich in bioactive components, primarily taurine, l-carnitine, choline, alpha-lipoic acid, conjugated linoleic acid, glutathione, creatine, coenzyme Q10 and bioactive peptides. Many studies have reported their antioxidant and health-promoting properties connected with their lipid-lowering, antihypertensive, anti-inflammatory, immunomodulatory activity and protecting the organism against oxidative stress. The antioxidant activity of meat components results, among others, from the capability of scavenging reactive oxygen and nitrogen species, forming complexes with metal ions and protecting cells against damage. This review is focused to gather accurate information about meat components with antioxidant and biological activity.